Acceptability and utilization of fortified balanced energy protein supplements among pregnant women in rural Nepal. - Lama, Tsering. (Tufts University. Tisch Library., 2020)
This presentation reports on a balanced energy protein supplementation trial in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy